Teaching choice‐making within activity schedules to children with autism. (10th July 2021) - Deel, Nicole M.; Brodhead, Matthew T.; Akers, Jessica S.; White, Allison N.; Miranda, David Ray G.
Abstract: Though the value of choice‐making opportunities in behavioral interventions is well established, specific demonstrations of its applications are limited. In this study, we first taught participants to independently complete two types of activity schedules: a choice activity schedule (i.e., one that allowed the participants to choose the sequence of activities) and a no choice activity schedule (i.e., one in which the sequence was predetermined by the researcher). Then, we evaluated participant preference between the before‐mentioned schedules, and a control activity schedule (i.e., baseline contingencies). Obtained preference was idiosyncratic across participants, highlighting the importance of individualized preference assessments in the context of play. Implications and future directions are discussed, including a refined framework for incorporating choice into independent activity schedule completion.